Adaption and psychometric evaluation of the Presentation of Online Self Scale in adults - N. Strimbu (Elsevier, 2021)
Introduction: The Presentation of Online Self Scale (POSS) is an established psychometric tool used to measure how an individual presents oneself in online environments. The POSS was originally used with an adolescent sample. This study aimed to develop a factor structure of the POSS for use with an adult sample as well as examine the reliability and convergent validity of the tool. Methods: A quantitative design was applied. Participants (n ​= ​531) aged 18–74 (M ​= ​35, SD ​= ​12.09) completed the POSS and the Ten-Item Personality Index (TIPI) that assessed personality traits. Results: Exploratory factor analysis revealed a three-factor solution of the POSS with an adult sample. The three factors explained 55% of the variance in POSS scores. All items had loadings ranging from 0.30 to 0.84. The new structure, renamed the Presentation of Online Self Scale for Adults (POSSA), showed satisfactory reliability and convergent validity. Conclusions: The findings of this study suggest that the three factor version of the POSS is a valid and reliable tool for measuring online self-presentation in adults. Self-presentation evolves through developmental stages, thus presenting the need for age appropriate psychometric instruments to fit those stages.